Electrodiagnostic findings in facial onset sensory motor neuronopathy (FOSMN). (August 2022) - De Oliveira, Hugo M.; Silsby, Matthew; Jaiser, Stephan R.; Lai, H. Ming; Pavey, Nathan; Kiernan, Matthew C.; Williams, Tim L.; Vucic, Steve; Baker, Mark R.
Highlights: Blink reflexes are abnormal in over 90% of patients with FOSMN. In FOMSN, upper motor neuron dysfunction is not evident clinically, but it can be detected in up to 50% of patients on neurophysiological testing. Upper limb somatosensory evoked potential central conduction times increase on interval testing in FOSMN and might be used for monitoring disease progression. Abstract: Objective: To determine the electrodiagnostic characteristics of facial onset sensory and motor neuronopathy (FOSMN). Methods: Electrophysiological data from 10 FOSMN patients in Newcastle-upon-Tyne and Sydney were reviewed. Relevant literature was reviewed. Results: Findings on standard electrophysiological assessment were in broad agreement with those published: blink reflexes were abnormal in all but one patient; sensory nerve action potentials were reduced but compound muscle action potentials preserved; mixed acute and chronic neurogenic change was identified on needle electromyography in bulbar and cervico-thoracic muscles in approximately 50% of patients. Upper limb somatosensory evoked potential (SEP) central conduction times were increased (n = 4) and progressed on repeat testing (n = 3). Upper motor neuron dysfunction was revealed by several measures [ipsilateral motor evoked potentials (MEPs) (n = 1); reduced short interval intra-cortical inhibition on threshold-tracking transcranial magnetic stimulation (n = 2); absent beta-band intermuscular coherence (n = 3)]. Conclusions: Electrodiagnostic investigation of FOSMN should include blink reflex testing, SEPs and tests of upper motor neuron function. The combination of progressive lower motor neuron disease and upper motor neuron disease on neurophysiological investigation provides further support for the contention that FOSMN is a rare variant of motor neurone disease. Significance: These findings will aid the neurologist and neurophysiologist in making a confident diagnosis of FOSMN, thus expediting appropriate care.